2018
DOI: 10.1186/s12864-018-4931-3
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of testis-specific long noncoding RNAs in mice

Abstract: BackgroundSpermatogenesis, which is the complex and highly regulated process of producing haploid spermatozoa, involves testis-specific transcripts. Recent studies have discovered that long noncoding RNAs (lncRNAs) are novel regulatory molecules that play important roles in various biological processes. However, there has been no report on the comprehensive identification of testis-specific lncRNAs in mice.ResultsWe performed microarray analysis of transcripts from mouse brain, heart, kidney, liver and testis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 47 publications
4
51
0
1
Order By: Relevance
“…3D). This is not unexpected, as these have been reported to be the two most highly represented categories among lncRNAs in general [17], and particularly in testis as well [29,35,38]. However, the proportion of AS lncRNAs overlapping protein-coding genes in our lists was surprisingly high in relation to the small proportion of the genome occupied by protein-coding genes (see Fig.…”
Section: Characterization Of Lncrnas In the Different Testicular Cellsupporting
confidence: 61%
See 2 more Smart Citations
“…3D). This is not unexpected, as these have been reported to be the two most highly represented categories among lncRNAs in general [17], and particularly in testis as well [29,35,38]. However, the proportion of AS lncRNAs overlapping protein-coding genes in our lists was surprisingly high in relation to the small proportion of the genome occupied by protein-coding genes (see Fig.…”
Section: Characterization Of Lncrnas In the Different Testicular Cellsupporting
confidence: 61%
“…An increasing number of studies have shown that lincRNAs can affect the expression of their neighbouring protein-coding genes or other target genes by acting through different mechanisms, either in cis or in trans [27,46,47]. Thus, in order to identify possible functional relations, different studies have correlated lincRNAs with neighbour mRNA loci located at varying distances such as <300 Kb [47], <100 Kb [48,49], <30 Kb [35], or <10 Kb [29], depending on the study.…”
Section: Co-expression Of Lncrnas With Overlapping and Neighbouring Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that lincRNAs can regulate gene expression in certain ways, including cis and trans [34,35]. Hong and Kwon used genomic analysis to identify protein-coding genes near (≤ 10 kb) testis-specific lincRNAs to predict the functions of lincRNAs [36]. Zhang and Chen predicted 1061 cis-regulated and 782 trans-regulated targets of DE lincRNAs in their study to explore the DE lincRNAs functions [37].…”
Section: Discussionmentioning
confidence: 99%
“…For ncRNAs to have an effect across generations, they must be physically transferred from the parents to the offspring via the germline. A large body of evidence demonstrates that male germ cells at mitotic, meiotic and post-meiotic stages and female gametes stably express thousands of ncRNAs [109][110][111]. An earlier RNA profiling study of human sperm led the authors to conclude that the male gamete is not only a vector of DNA but also appears to contribute to the initial transcriptome of the fertilized egg [112,113].…”
Section: Epigenetic Control Mediated By Short and Long Non-coding Rnasmentioning
confidence: 99%